A silver lining to REDD: Institutional growth despite programmatic failure. Issue 1 (29th December 2020) - Borgerhoff Mulder, Monique; Caro, Tim; Ngwali, Assa Sharif
Abstract: What happens when conservation interventions ostensibly fail? We outline a REDD+ intervention on Zanzibar, Tanzania which is adapting to a failure to implement carbon compensation payments and to the increased global price of cloves. Using a mix of quantitative and qualitative methods we provide preliminary evidence that well‐managed shehia (wards) with registered Community Forestry Management Agreements (CoFMAs) are slowing their rates of deforestation. We also find an increase in the number of shehia with CoFMAs despite the absence of carbon payments. Using this island‐wide case study we make inferences about the mechanisms whereby institutional expansion has occurred in ways consistent with cultural evolutionary dynamics of institutional change. We draw lessons for planning and practice that may help with the design of future conservation interventions and with bolstering the morale and effectiveness of disappointed partners.